2019
DOI: 10.3390/met9121339
|View full text |Cite
|
Sign up to set email alerts
|

Copper Extraction from Black Copper Ores through Modification of the Solution Potential in the Irrigation Solution

Abstract: This article presented the behavior of ores containing black copper under acid leaching. The solution potential was modified by adding agents, and five leaching conditions were evaluated, one as a control based on sulfuric acid leaching (conventional), and the others by changing the solution potential with: ferrous sulfate (FeSO4), white metal (Cu2S), sulfur dioxide (SO2), and ozone (O3). Leaching behavior was evaluated with laboratory bottle (ISO-pH) and column leaching tests. Two ores samples from the Lomas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The authors found that when an Fe 3 O 4 /MnO 2 ratio of 2/1 or higher is used, other variables (H 2 SO 4 concentration, particle size, agitation speed, leaching time) are irrelevant when obtaining Mn dissolutions of around 80%. There are few studies on black copper minerals, and recent studies report Cu and Mn recovery when Fe-reducing agents are added [3,20,24]. Benavente et al [24] added ferrous ions to acid in order to reduce leaching of black copper minerals and found that the dissolution of MnO2 immediately promoted Cu dissolution in black copper minerals.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found that when an Fe 3 O 4 /MnO 2 ratio of 2/1 or higher is used, other variables (H 2 SO 4 concentration, particle size, agitation speed, leaching time) are irrelevant when obtaining Mn dissolutions of around 80%. There are few studies on black copper minerals, and recent studies report Cu and Mn recovery when Fe-reducing agents are added [3,20,24]. Benavente et al [24] added ferrous ions to acid in order to reduce leaching of black copper minerals and found that the dissolution of MnO2 immediately promoted Cu dissolution in black copper minerals.…”
Section: Overviewmentioning
confidence: 99%
“…There are few studies on black copper minerals, and recent studies report Cu and Mn recovery when Fe-reducing agents are added [3,20,24]. Benavente et al [24] added ferrous ions to acid in order to reduce leaching of black copper minerals and found that the dissolution of MnO2 immediately promoted Cu dissolution in black copper minerals. Pérez et al [20] proved that the Fe 3 O 4 in tailings can be an efficient reducing agent of MnO 2 in black copper minerals when working with high concentrations, but showed lower dissolution kinetics regarding ferrous ions.…”
Section: Overviewmentioning
confidence: 99%
“…There are few studies that investigated leaching of black copper minerals [16][17][18][19]. In the investigations carried out by Benavente et al, [18] and Pérez et al, [16] it was discovered that working in an acid-reducing leaching favors dissolution of MnO2, thus favoring the extraction of copper.…”
Section: Introductionmentioning
confidence: 99%
“…Exotic deposits can be found in northern Chile near copper porphyry systems from the Paleogene period, such as Huanquintipa (Collahuasi), Quebrada Ichuco (El Abra), Mina Sur (Chuquicamata), and Damiana (El Salvador) [9,10]. Black copper appears in "wad" or "pitch" form in compact earthy botryoidal masses, or filling fractures and cementing gravel [11]. When it appears alone in an earthy state, it is called wad, while when it is associated with chrysocolla, it is called pitch or black chrysocolla [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Some reducing agents proposed for dissolving refractory minerals under conventional conditions are white metal (Cu 2 S) [11], sulfur dioxide (SO 2 ) [6,11,[18][19][20][21][22], ferrous sulfate (FeSO 4 ) [23][24][25], sponge iron [26], hydrogen peroxide [27,28], and even pyrite [29], several of which have been evaluated for industrial application as treatment alternatives. The SO 2 and Cu 2 S present better performance, although the use of SO 2 is complex from the safety and environment point of view and Cu 2 S availability is limited for small-scale mining; the reagent to be evaluated is FeSO 4 , which is easy to access and manage.…”
Section: Introductionmentioning
confidence: 99%